Detection of dermatophytes in the environment of a podiatry clinic - Sabino, Raquel (2017)
Podiatry is a healthcare profession that specializes in the management of disorders of the lower limb and foot. Podiatric treatments have the potential to generate substantial concentrations of organic dusts. Occupational exposure to bioaerosols in podiatry clinics has been studied, but it was never accessed in a deeply manner for fungi. The detection of dermatophytes in podiatric clinics is a matter of concern since the environmental presence of these fungi can contribute to spread the infection to podiatry workers and to other patients consulted in the podiatry clinics. The aim of the present study was to characterize the dermatophyte burden during podiatric activities by the use of cultural methods but also molecular methodologies for fungal DNA detection directly from the collected samples.